2020
DOI: 10.1002/ccd.29090
|View full text |Cite
|
Sign up to set email alerts
|

One‐year outcomes of supersaturated oxygen therapy in acute anterior myocardial infarction: The IC‐HOT study

Abstract: Background Supersaturated oxygen (SSO2) has recently been approved by the U.S. Food and Drug Administration for administration after primary percutaneous coronary intervention (pPCI) in patients with anterior ST‐segment elevation myocardial infarction (STEMI) based on its demonstration of infarct size reduction in the IC‐HOT study. Objectives To describe the 1‐year clinical outcomes of intracoronary SSO2 treatment after pPCI in patients with anterior STEMI. Methods IC‐HOT was a prospective, open‐label, single‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Subanalysis of the IC-HOT trial also showed similar reductions in LV volumes measured over 30 days as in the 2005 AMIHOT I substudy by Warda et al ( 51 ), confirming that early SSO 2 therapy reduces adverse LV dilatation (remodeling) during the healing phase of infarction ( Figure 8 ). These data suggest that infusion of SSO 2 therapy following primary PCI in patients with anterior STEMI is safe and may improve 1-year clinical outcomes ( 57 ), although a randomized trial adequately powered for clinical events is required to determine the long-term consequences of this therapy.…”
Section: Sso 2 Oxygen Therapy: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Subanalysis of the IC-HOT trial also showed similar reductions in LV volumes measured over 30 days as in the 2005 AMIHOT I substudy by Warda et al ( 51 ), confirming that early SSO 2 therapy reduces adverse LV dilatation (remodeling) during the healing phase of infarction ( Figure 8 ). These data suggest that infusion of SSO 2 therapy following primary PCI in patients with anterior STEMI is safe and may improve 1-year clinical outcomes ( 57 ), although a randomized trial adequately powered for clinical events is required to determine the long-term consequences of this therapy.…”
Section: Sso 2 Oxygen Therapy: Clinical Studiesmentioning
confidence: 99%
“…(Bottom) Preclinical studies showed several beneficial effects of SSO 2 therapy; (Fourth Panel, Clinical Studies) (Top) Summary of consistent infarct size reduction trials conducted by TherOx, Inc ( 40 , 50 , 55 ); (Bottom) one-year propensity-matched IC-HOT data demonstrating no death, no new onset heart failure (HF), and no HF hospitalizations with SSO 2 therapy; chart supplied by G.W. Stone from data in Chen et al ( 57 ); (Fifth Panel, FDA Approval, 2019). FDA = Food and Drug Administration; IC-HOT = Intracoronary Hyperoxemic Oxygen Therapy study; INFUSE-AMI = The INFUSE-Anterior Myocardial Infarction (AMI) study; RBC = red blood cell; STEMI = ST-segment elevation myocardial infarction.…”
mentioning
confidence: 99%
“…With this approach, SSO 2 therapy reached better long-term clinical outcomes—composite of all cause-death or new-onset HF or HF hospitalization at 1 year—compared with the control group (0% vs. 12.3%; p = 0.01). Also, the rate of stent thrombosis was numerically higher in the control group compared with the SSO 2 group (1.2% vs. 4.9%, p = 0.17) [ 64 ].…”
Section: Supersaturated Oxygenmentioning
confidence: 99%
“…Chen et al present 1-year clinical outcomes of the IC-HOT study (February 2016-May 2017). 5 This was an open-label, single-arm study of 100 patients for assessing the safety of intracoronary "optimized" SSO2 delivery in acute anterior MI. The SSO2 delivery was 100 cc/min for 60 minutes initiated after successful PCI with TIMI 2 or 3 flow, through withdrawal of blood from a femoral sheath that is oxygenated to a PaO2 of 760-1,000 mmHg and infused into the origin of left main coronary artery using.…”
Section: In This Issue Of Catheterization and Cardiovascular Interventionsmentioning
confidence: 99%
“…In this issue of Catheterization and Cardiovascular Interventions , Chen et al present 1‐year clinical outcomes of the IC‐HOT study (February 2016–May 2017) 5 . This was an open‐label, single‐arm study of 100 patients for assessing the safety of intracoronary “optimized” SSO2 delivery in acute anterior MI.…”
mentioning
confidence: 99%